A demonstration of the being and attributes of God and other writings - Clarke, Samuel (Cambridge texts in the history of philosophy, 1998)
Samuel Clarke was by far the most gifted and influential Newtonian philosopher of his generation, and A Demonstration of the Being and Attributes of God, which constituted the 1704 Boyle Lectures, was one of the most important works of the first half of the eighteenth century, generating a great deal of controversy about the relation between space and God, the nature of divine necessary existence, the adequacy of the Cosmological Argument, agent causation, and the immateriality of the soul. Together with the other texts presented in this edition, it also provides the best introduction to Clarke's philosophical views, which, in addition to their intrinsic interest, are historically important for the light they shed both on the philosophical positions within the Newtonian circle and on the exchange between Clarke and Leibniz, the most famous philosophical controversy of the eighteenth century.